2019
DOI: 10.1093/jnci/djz015
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Hysterectomy and Ovarian Cancer Risk: A Population-Based Record-Linkage Study

Abstract: Background Recent studies have called into question the long-held belief that hysterectomy without oophorectomy protects against ovarian cancer. This population-based longitudinal record-linkage study aimed to explore this relationship, overall and by age at hysterectomy, time period, surgery type, and indication for hysterectomy. Methods We followed the female adult Western Australian population (837 942 women) across a 27-y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
39
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 31 publications
6
39
1
5
Order By: Relevance
“…The exposures of interest were hysterectomy and oophorectomy for benign indication, defined using procedure codes from the HMDC, as we had done in a previous publication (Supplemental Table 3). 17 Oophorectomy was categorized as none, unilateral, or bilateral. Women who had an oophorectomy more than 6 months before or after their hysterectomy were categorized as having a separate oophorectomy.…”
Section: Variables Of Interestmentioning
confidence: 99%
“…The exposures of interest were hysterectomy and oophorectomy for benign indication, defined using procedure codes from the HMDC, as we had done in a previous publication (Supplemental Table 3). 17 Oophorectomy was categorized as none, unilateral, or bilateral. Women who had an oophorectomy more than 6 months before or after their hysterectomy were categorized as having a separate oophorectomy.…”
Section: Variables Of Interestmentioning
confidence: 99%
“…However, according to a report from Sweden, in women hospitalized for a diagnosis of endometriosis, the risk ratio of ovarian cancer was 1.54 without hysterectomy and 1.05 with hysterectomy, with hysterectomy eliminating the risk of ovarian cancer [ 20 ]. In addition, in a study reported in 2019 that followed 830,000 women for 27 years, hysterectomy without oophorectomy reduced the risk of ovarian cancer to HR 0.17 in women with endometriosis [ 41 ]. Thus, the risk of developing EAOC was reduced with hysterectomy rather than cystectomy of ECs.…”
Section: Clinical Epidemiologymentioning
confidence: 99%
“…Evidence suggests that performing a hysterectomy while preserving the ovaries may help to prevent the development of ovarian cancers in women. Report from Dixon-Suen et al on a study carried out on 837 942 women from Western Australia, demonstrated that in women diagnosed with endometriosis or fibroids, a hysterectomy significantly reduced their overall risks for developing ovarian cancers (HR = 0.17, 95% CI = 0.12-0.24, and HR = 0.27, 95% CI = 0.20-0.36, respectively) [42] . Furthermore, in some cases of endometriosis, cystectomies may also aid in preventing cancer development [43] .…”
Section: Association Between Endometriosis and The Development Of Ovarian Cancersmentioning
confidence: 99%